Experience in the use of tocilizumab in patient with systemic juvenile idiopathic arthritis and type 1 diabetes - E. A. Ligostaeva; N. A. Tsurikova (Педиатрическая фармакология)
The article describes the experience of using tocilizumab in a patient with systemic juvenile idiopathic arthritis (JIA) refractory to therapy with classical immunosuppressants, coupled with type 1 diabetes. Already after the first injection of tocilizumab there was a decrease in the severity of the disease’s systemic manifestations, pain in the affected joints and functional disorders. A 30% improvement by JADAS index, ACRPedi was reached. By the 8th week of therapy, proliferative changes in wrist joints and arthralgias reduced and the duration of morning stiffness decreased. After 3 months, JIA’s activity decreased (DAS 28 scale); erythrocyte sedimentation rate and serum concentrations of C-reactive protein decreased; hemoglobin concentration and the number of erythrocytes increased. After 6 months of treatment, clinical and laboratory remission (DAS 28 < 2.6) started. On the background of tocilizumab treatment, systemic manifestations of the disease stopped, laboratory and articular JIA’s activity decreased and there was no need for the introduction of glucocorticoids. There also has been a positive dynamics of glycemia, which allowed reducing the dose of insulin. There were no adverse events during treatment with tocilizumab. The disease’s activity on a visual analog scale has also decreased, as well as functional insufficiency by Children Heals Assessment Questionnaire.